Comprehensive Physiology 1995
DOI: 10.1002/cphy.cp110109
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression and Protein Degradation

Abstract: Chromatin proteins and cellular aging The relationship between aging and protein synthesis RNA synthesis Protein synthesis and degradation during aging and senescence Aging and transcription Age-related changes in protein synthesis Enzymes, enzyme alteration, and protein turnover Age-related changes in the structure and function of chromatin Macromolecular methylation during aging The effect of age and nutrition on protein synthesis by cells and tissues from mammals Levels of specific messenger RNA species as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
46
1

Year Published

1997
1997
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 390 publications
0
46
1
Order By: Relevance
“…Proper proteome dynamics are critical to normal development and maintenance of health (7,8). For example, the dysregulation of protein turnover has been implicated in the aging process (9), increased degradation of the cystic fibrosis transmembrane conductance regulator (CFTR) chloride channel is a primary cause of cystic fibrosis (10), and the inability to clear protein aggregates leads to pathogenic accumulations in Alzheimer's, Parkinson's, Creutzfeldt-Jakob, and other age-related diseases (11).…”
mentioning
confidence: 99%
“…Proper proteome dynamics are critical to normal development and maintenance of health (7,8). For example, the dysregulation of protein turnover has been implicated in the aging process (9), increased degradation of the cystic fibrosis transmembrane conductance regulator (CFTR) chloride channel is a primary cause of cystic fibrosis (10), and the inability to clear protein aggregates leads to pathogenic accumulations in Alzheimer's, Parkinson's, Creutzfeldt-Jakob, and other age-related diseases (11).…”
mentioning
confidence: 99%
“…Virtually all cross-sectional studies of mammalian aging have been interpreted as though they were performed longitudinally (e.g. see the studies and discussion of the studies in Van Remmen et al ., 1995). The effects of LTCR are almost always assumed to have resulted from incremental resistance to essentially irreversible damage.…”
Section: Widespread Views Of Aging Have Slowed the Development Of Lonmentioning
confidence: 99%
“…A general age-associated decline in the function of multiple proteins has been correlated with several types of posttranslational modifications, particularly oxidation, glycation, isomerization, deamidation, racemization, and cross-linking (1)(2)(3). Although the exact processes leading to the increase in these dysfunctional proteins remains undefined, it has been suggested that the greater accumulation of such modifications with age may result, at least in part, from the diminished capacity of the cell for the removal and replacement of defective proteins.…”
mentioning
confidence: 99%
“…However, a number of studies also report conflicting results, due perhaps to the complications inherent in measurements of total protein turnover, which represent weighted averages from a complex mixture of turnover rates (reviewed in Ref. 3). …”
mentioning
confidence: 99%
See 1 more Smart Citation